Anthropology of levitation. A path through the thinking of Peter Sloterdijk (Nóema, 2013)
In the following writing we desire to converse with the mature thought of one of the most absorbing and creative living philosopher, the German Peter Sloterdijk. Our expedition will investigate his original portrait of the man, as it emerges by a confrontation among the perspective of the author himself with those of Martin Heidegger and Arnold Gehlen, respectively. In particular, our intent is to explore the different aspects of the relationship between the concept of sphere and this living being that we are.
Keywords: Sloterdijk; Heidegger; Gehlen; anthropology; sphere; Lichtung; humanism; space; world; environment